Making it Relevant: Reflections on the Teaching of Brazilian Theatre in the United States - Albuquerque, Severino J. (Latin American Theatre Review, 2017)
With a focus on the relevance of Brazilian theatre in the United States, this article aims to gauge the diversity of challenges faced by those involved in the teaching of it in US colleges and universities and the staging of scenes or entire plays in those institutions and other venues. Attention is also given to related factors such as the availability of translated texts, the linguistic background and teaching and learning goals of instructors and students, the directorial vision of those in charge of stagings, and the ever present obstacle of a less commonly spoken language, as is the case of Portuguese in the US. Conclusions presented here were made possible by those colleagues who answered my email queries and/or responded to the brief questionnaire sent them, the text of which is reproduced in Appendix I. Appendix II is an account by the co-directors of a specific staging, that of Qorpo Santo’s As Relações Naturais at the University of Wisconsin-Madison in the spring of 2008.